The Decision to Use Public Internet Services to Access Digital Content in Thailand - Anaspree Chaiwan (Faculty of Economics Chiang Mai University, 2020)
Chiang Mai University Journal of Economics (CMJE) is a double-blind peer-reviewed journal published by the Faculty of Economics, Chiang Mai University, Thailand which aims to be a channel to report academic progression in the field of economics. It was established in 1996 and has been indexed in the Thai-Journal Citation Index TCI Tier 1 since 2017